Structures & construction in historic building conservation - Forsyth, Michael, 1951- (Historic building conservation., 2007)
"This present volume - Structures & Construction in Historic Building Conservation - traces the history of structures in various materials and contains guidance on the survey, assessment and diagnosis of structures, and the integration of building code requirements within the historic fabric." "It discusses conservation engineering philosophy, exposes the conflict between building codes and conservation legislation, and offers solutions. Leading-edge, on-site metric survey techniques are described and a range of structural advice is given, including methods of repair in relation to philosophical principles. Causes of induced movement in historic buildings are explained, together with basic soil mechanics and the assessment and diagnosis of structural failure. Chapters also cover the conservation of different types of construction: masonry, iron and steel, and concrete and reinforced concrete."--Jacket.